CONTROL OF STAPHYLOCOCCUS AUREUS ACTIVITY IN RATS USING ELECTROMAGNETIC SIGNALS AT RESONANCE FREQUENCY "IN VIVO STUDY - Hussein Hussein. A. Motaweh; Fadel M.Ali; Ahmed M.El-Khattib; Soraya A.Sabry; Sahar E.Abo-Neima (European Scientific Journal, ESJ, 2014)
In this work, the frequency of electric impulses that interfere withthe bioelectric signals generated during staphylococcus aureus (S.aureus)cellular division is investigated. The experiment was expanded to in vivostudy for the obtained data in which rats were infected with S.aureus andthen whole body exposure were exposed to square electric pulses (SEP) thatcauses inhibition to the microbial cellular growth. Another group of animalswas infected by previously inhibited bacteria with SEP then the histologicaland molecular structures of the liver were investigated for all the animalgroups, Dielectric relaxation studies for the liver in the frequency range 42KHz-5MHz was used to determined molecular structure changes.The results indicated a highly significant inhibition of cellular growth forS.aureus in addition to pronounced changes in the cellular morphology afterthe exposure of the micro-organism to the resonance frequency of 0.8 HzSEP for 120 minutes. From the histological and dielectric relaxationmeasurements and results it was indicated that the liver for animals infectedby S.aureus and then exposed to SEP showed significant improvement intheir health state as compared with infected and non exposed group.Moreover, the liver for the animals infected with previously treated bacteriawith SEP showed highly significant decrease in cellular damage as compared with untreated bacteria. It was concluded that treatment ofS.aureus by 0.8 Hz SEP acts on the structure and biological activity ofthe bacteria and it is a promising methodology to control S.aureus activity invivo and in vitro applications.